2016
DOI: 10.1155/2016/1604609
|View full text |Cite
|
Sign up to set email alerts
|

Usability Pitfalls of Diabetes mHealth Apps for the Elderly

Abstract: Diabetes mellitus has high prevalence in the ageing population and is often accompanied by other comorbidities, such as Alzheimer's disease, and general disabilities, such as poor eyesight. These comorbidities have redefined ways in which patients use mHealth apps, including diabetes apps. The latter have proven benefits for monitoring blood glucose levels and insulin tracking in the general population. In this paper, we analyse a diabetes monitoring app DeStress Assistant (DeSA), which was developed as a part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0
16

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 16 publications
4
68
0
16
Order By: Relevance
“…Meeting appropriate usability criteria for included features determines patient engagement, optimal benefit of an intervention, and an understanding of generalizability [22]. Isaković’s research showed that app features developed for the general population are not necessarily suitable for elderly users [23]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meeting appropriate usability criteria for included features determines patient engagement, optimal benefit of an intervention, and an understanding of generalizability [22]. Isaković’s research showed that app features developed for the general population are not necessarily suitable for elderly users [23]. …”
Section: Introductionmentioning
confidence: 99%
“…Isaković et al [23] recruited older adults to evaluate diabetes app they developed for general diabetic patients, reporting that elderly users had difficulty using the app. Arnhold et al [20] performed an expert-led usability test of general diabetes apps for patients age 50 years or older; with results showing moderate to good usability.…”
Section: Introductionmentioning
confidence: 99%
“…[37] Another study also showed that older adults were less likely than younger adults to value the importance of Patient Health Records (PHRs). [31] There might be several reasons behind these findings including: a) greater ease of use and comfort with technology among younger adults, [38] b) poor usability, availability, and accessibility of HIT functions tailored to the elderly, [39][40][41] c) lower health literacy in the elderly, [42,43] d) lower educational attainment and income in the elderly, [3,44] and e) unique challenges from having chronic diseases that are more prevalent in the elderly that impede use of technology (e.g. arthritis, vision impairment etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions should include the elderly as part of the stakeholder group, or critical factors that are necessary to address the real problem may be overlooked. This may result in poor adoption and inefficient use of technology [40]. Interventions should include new perspectives and use patients' tactic knowledge [40].…”
Section: Significant Factorsmentioning
confidence: 99%
“…This may result in poor adoption and inefficient use of technology [40]. Interventions should include new perspectives and use patients' tactic knowledge [40].…”
Section: Significant Factorsmentioning
confidence: 99%